INCOME: A MEASUREMENT OF CURRENTLY ADDED PURCHASING POWER THROUGH OPERATIONS. - Raun, Donald L. (The Accounting Review, 1952)
Abstract Accounting uses a universally known measuring stick, the dollar. Yet the common dollar is not an invariant measuring unit. Dollars in 1950 do not measure the same purchasing power as did 1940 dollars. Accounting, in other words, assumes a stable measuring unit. In periods of major price movements this assumption is clearly invalid for certain purposes, as has been pointed out by various writers in recent years. Undoubtedly interpretive accounting faces a challenge at this point. Management and accountants should remember that their primary responsibility is still to the investors, those who seem to be the forgotten men. The absentee investor, unlike the owner-operator, has no opportunity to combine reported information with first hand knowledge of the conditions and activities of the business. Management and accountants have the responsibility to provide information to aid the stockholder in wise decisions. The stockholder requires information to aid him in decisions to hold, sell or buy more stock, in other words, information concerning the comparative merits of his stock and alternative investment opportunities.